Penerapan Teknik Relaksasi Genggam Jari terhadap Penurunan Skala Nyeri pada Pasien Post Operasi Appendektomi di Ruang Bedah AN NASR RS Ibnu Sina Makassar - Hijaz Muhammad; Simanjuntak Machdalena; S Dedi; Munir Wahyuni Nur; Rasyidin Zahi; Idayanti Idayanti (Wal'afiat Hospital Journal, 2026)
Postoperative patients are individuals who are in the postoperative period and require monitoring as they regain consciousness following anesthesia. Every surgical procedure involves an incision, which causes tissue trauma and may result in pain. Pain is the body’s response to a noxious stimulus. The Finger Grasp Relaxation technique is administered to postoperative patients approximately 6–7 hours after the administration of analgesic medications, whose effects typically last for 2–4 hours. This relaxation technique is performed once daily for 15 minutes and is provided for a minimum of three days. The Five-Finger Grasp Relaxation technique is effective in reducing pain in postoperative patients, except in those who have wounds on the palms of the hands or the soles of the feet, for whom the therapy is contraindicated. The purpose of this scientific paper is to determine the implementation of the Five-Finger Grasp technique in postoperative patients experiencing nursing problems related to pain in the Surgical Ward of Ibnu Sina Hospital in 2025, with the aim of improving patient comfort. This scientific paper employs a case study design. The subject consisted of a postoperative patient with nursing problems related to pain. Data analysis was conducted using descriptive analysis. The results of the implementation showed that after the application of the Five-Finger Grasp Relaxation technique, pain intensity decreased in the subject.